IR-transparent Y2O3 ceramics: Effect of zirconia concentration on optical and mechanical properties - Dariia Chernomorets; Pietro Galizia; Giacomo Zanetti; Stefano Varas; Alessandro Chiasera; Andreana Piancastelli; Roman Yavetskiy; Jan Hostaša (Open Ceramics)
Y2O3 transparent ceramics with different amounts of ZrO2 were obtained by reactive vacuum sintering at a relatively low temperature of 1735 °C for 22 h. The influence of ZrO2 concentration within the 0–15 mol.% range on the microstructure, phase composition, microhardness, and optical properties of ceramics in the visible and IR ranges was investigated. SEM and XRD results indicate the absence of secondary phases in the studied concentration range, indicating the formation of single-phase solid solutions. It was shown that doping by ZrO2 considerably decreases the average grain size of ceramics, while microhardness has the opposite behaviour. 15 mol.% ZrO2-doped Y2O3 ceramics demonstrated the highest transmittance in the visible wavelength range. On the other hand, 5 and 7 mol.% ZrO2-doped Y2O3 could be considered promising materials for the first atmospheric window (3–5 μm).